Chemical constituents, antioxidant and antifungal activities of the essential oil from Vietnamese Ocimum tenuiflorum L. leaves - Thi-Hoan Luong; Huu-Khanh-Tan Tran; Woo-Jin Jung; Van-Viet Nguyen; Dang-Minh-Chanh Nguyen (Vietnam Journal of Science, Technology and Engineering, 2024)
In this study, the authors aim to determine the chemical compositions of the essential oil from Ocimum tenuiflorum leaves and to evaluate its antioxidant and antifungal activities. The essential oil used in this research, extracted by hydrodistillation, was chemically profiled using gas chromatography/mass spectrometry (GC/MS) analysis. Methyl eugenol (46.07%), caryophyllene (15.65%), eugenol (11.83%), β-elemene (4.33%), β-copaene (4.18%), caryophyllene oxide (3.18%), and α-copaene (1.95%) were identified as major components of the essential oil. The results indicated that the essential oil of O. tenuiflorum leaves possessed relatively high 2,2-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azinobis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging activities with IC50 values of 53.5 and 55.1 µg/ml, respectively, compared with 67.2 and 63.2 µg/ml, respectively, for the positive control. The reducing powers of O. tenuiflorum essential oil and butylated hydroxytoluene (BHT) at a concentration of 200 µg/ml were 0.95 and 0.73, respectively. Additionally, the essential oil of O. tenuiflorum at a concentration of 200 µg/ml strongly inhibited the mycelial growth of Rhizoctonia solani.